The role of controlled hypotension upon transfusion requirement during maxillary downfracture in double-jaw surgery - VAROL, ALTAN (CHURCHILL LIVINGSTONE, 2010)
Introduction: To evaluate the role of induced hypotension during maxillary downfracture osteotomy on the requirement for blood transfusion, duration of operation and induced anaemia in bimaxillary surgery. Material and methods: 45 young orthognathic patients were operated under hypotensive anaesthesia between 2004 and 2006. Operations were LeFort I osteotomies (n=45), bilateral sagittal split osteotomies (BSSO) (n=42), segmental osteotomies (n=3), tongue reduction (n=1), genioplasties (n=15), digastric myotomies (n=2), and bone grafts were the supplementary procedures. Pre-postoperative haemograms, intraoperative blood loss, and duration of operations were the studied parameters. Statistical analysis was performed using SPSS 11.5 for Windows. Results: None of the patients received a blood transfusion. Mean blood loss was 377 +/- 111.2 mL with the range of 180 mL to the maximum of 625 mL. Mean duration was 267.1 +/- 61.2 min with minimum of 180 min and maximum of 400 min. Mean preop Hb level was 14 +/- 1.9 g/dL with the range from 10.3 g/dL to a maximum of 17.2 g/dL. Mean postop Hb level was 11.8 +/- 2 g/dL with a range of 8.2-16.2 g/dL levels. Preop erythrocyte counts were 435.3 +/- 18.2 and 416.4 +/- 16.1 (x 104/mcL) on the first postop day. Conclusion: Transfusion in bimaxillary orthognathic surgery could be prevented by induction of hypotension during maxillary downfracture. (C) 2009 European Association for Cranio-Maxillo-Facial Surgery
Keywords: controlled moderate hypotension; transfusion; maxillary downfracture; blood loss; haemoglobin; haematocrit; bimaxillary surgery; FORT-I OSTEOTOMY; ORTHOGNATHIC SURGERY; BLOOD-LOSS; DELIBERATE HYPOTENSION; ANESTHESIA; COMPLICATION; BLINDNESS